The great New York subway map - Ponzi, Emiliano (The Museum of Modern Art in association with the New York Transit Museum, 2017)
"... tells the fascinating story of the map's creation by the great Italian designer Massimo Vignelli and introduces young readers to the idea of graphic design as a way to solve problems and shape our world."--publisher.